CLINICAL CASE:: DEVELOPED NON-IMMUNE FETAL EDEMA CAUSED BY URAXUS FLOW - Pulatova, G.A.; Yusupbayev , R.B. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Fetal edema syndrome is a polyetiological disease characterized by pathologically excessive fluid accumulation in the serous cavities and soft tissues of the fetus. Fetal edema syndrome is the final stage of a number of intrauterine diseases. The prevalence of the disease is 1 in 1000-14000 births. Typically, no more than 20-33% of babies born with this diagnosis survive. Only with the use of modern medical technologies in the antenatal period and intensive care of babies in the neonatal period, this figure reaches 80%. Material and method: Patient M., 37 years old, 2nd pregnancy, 1st pregnancy complicated by a 6th week of gestational age termination. Due to the diagnosis of non-immune fetal edema at the place of residence, she applied to the RIAGIATM center and was hospitalized. Non-immune fetal edema was first detected at the 25th week of gestation. At the 26th week of gestation, an ultrasound examination was performed at the fetal medicine department of the RIAGIATM center and non-immune fetal edema (developed ascites, hydrocele, moderate hyponatremia, cardiomegaly, centralization of blood circulation, compensated right ventricular failure) was detected. Initially, diagnostic cordocentesis and amniocentesis, diagnostic and therapeutic fetal laparocentesis were performed, due to the high content of pro-inflammatory mediators in the ascitic fluid, the pregnant woman was treated with anti-inflammatory and immunoglobulin therapy. Due to recurrent ascites, the woman underwent a total of 3 laparocentesis procedures and 250-300 ml of ascitic fluid was evacuated in a row. During a follow-up ultrasound examination, the patient was diagnosed with recurrent non-immune fetal edema at 29 weeks of gestation and was hospitalized for a planned abdomino-amniotic shunting procedure. On the same day, an emergency cesarean section was performed due to severe placental abruption. The baby had no vital signs and was assessed with an Apgar score of 0/0. During the postnatal pathological examination, the fetus was found to have lower urinary tract anomalies - urethral atresia, bladder hypertrophy, and cystic fistula of the upper 1/3 of the urachus.